miR-145 Contributes to the Progression of Cervical Carcinoma by Directly Regulating FSCN1 - Ma, Li (Cell Transplant, 2019)
The purpose of our study was to investigate the underlying mechanism and functional role of microRNA-145 (miR-145) in cervical cancer. In this study, quantitative real-time PCR (qRT-PCR) was used to detect miR-145 and FSCN1 expression levels in tissues and HeLa cells. Western blotting was performed to determine the protein level of FSCN1. The luciferase assay was used to verify the direct target of miR-145. The CCK-8 assay and 2D colony formation assays were performed to determine the effects of miR-145 mimics or FSCN1 silencing on cell proliferation. miR-145 expression levels were significantly down-regulated, while FSCN1 expression levels were significantly up-regulated in the cervical carcinoma tissues compared with their matched non-cancerous tissues. In addition, FSCN1 expression levels were negatively correlated to miR-145 in tissues. Next, FSCN1 was verified as the direct target of miR-145 in HeLa cells. Moreover, overexpression of miR-145 dramatically inhibited the proliferation of HeLa cells. The silencing of FSCN1 exhibited the similar patterns on cell proliferation as miR-145 overexpression. The miR-145/ FSCN1 axis contributes to the progression of cervical cancer by inhibition of cervical cancer cell proliferation.